Answer:
The following are the solution to this question:
Step-by-step explanation:
Total energy capacity EN from adjacent ions is:
![\to EN= - (C)/(r)+De^{((-r)/(p))}.............(1)](https://img.qammunity.org/2021/formulas/chemistry/college/s12bpfmzrapebticvcty21zv8viyv9p3zp.png)
where the value of "C, D, and "r is constants.
In point a:
Differentiating EN:
![\to (d(EN))/(dr) = (C)/(r^2)+D e^-(r)/(p)(^(-1)/(p))](https://img.qammunity.org/2021/formulas/chemistry/college/z6rdbb0kqgov189kjj70nue7j065y5fpve.png)
![=(C)/(r^2)-(D)/(p)e^(-r)/(p)](https://img.qammunity.org/2021/formulas/chemistry/college/vm054i80npcnnm5j0stnhwazb1hz3zecd2.png)
In point b:
The above equation is equal to zero to get the value of C:
![\to (C)/(r^2)-(D)/(p)e^(-r)/(p)=0 \\\\\to C= (D r^2)/(p)e^(-r)/(p) \ \ \ \ or \ \ \ \ D= (C p)/(r^2)e^(-r)/(p)](https://img.qammunity.org/2021/formulas/chemistry/college/iu7jwcrjbqk6tli1cyswtrnemqfftjv49y.png)
The
value is replaced by the C value in (1):
![\to E_0= (1)/(r_0) (Dr_0^2)/(p).e^-(r_0)/(p) +D e^-(r_0)/(p)\\\\](https://img.qammunity.org/2021/formulas/chemistry/college/80wijxnrrxt0wwi293pap45ok8x511fn91.png)
![= D e^-(r_0)/(p)( {1-(r_0)/(p)})](https://img.qammunity.org/2021/formulas/chemistry/college/5quvnptvzbozxr1q2itidpm5e9hzaldu51.png)
The
value is replaced by the D value in (1):
![\to E_0= -(C)/(r_0) (C p )/(r_0^2).e^(r_0)/(p)](https://img.qammunity.org/2021/formulas/chemistry/college/cxhvu2m5vm2t1s5rppd4stt9xtdxph9pce.png)
![= (C)/(r_0)( {\frac{p} {r_0} -1})](https://img.qammunity.org/2021/formulas/chemistry/college/k8kkqpvpvz8doi69h8kablqza99ug2a29p.png)